A SACRED CELESTIAL MOTIF: AN INTRODUCTION TO WINGED ANGELS ICONOGRAPHY IN IRAN - Mazloumi, Yasaman; Nasrollahzadeh, Cyrus (PEOPLE: International Journal of Social Sciences, 2017)
Through history many motifs have been created and over the centuries, some of them turned into very well-known symbols. One of these motifs is winged angel. This sacred and divine creature which appears in human-shaped, serves intermediaries between the God and people, and during history, indicates legitimating and bestows God-given glory. This article aims to present the results of exploring the historical background of the winged angels in Iran, in order to understand its precise concept; where it comes from and what it resembles. For this aim, its conceptual and figurative evolution from ancient times till contemporary era is taken into consideration. Examination of the winged angel indicated that Ancient samples and Qajari instances are similar to each other regarding their appearance, gender and general pattern. However, they show major differences in their function and perception of their original meaning. Within this respect the illustrators of Qajar era were successful in copying the ancient samples in appearance but they incorporate a very new and different meaning: While ancient samples used them in kingly scenes and emphasized on bestowing glory and Farr, the Qajari ones displayed them in a very general form.